Economic evaluation of tislelizumab versus chemotherapy as second-line treatment for advanced or metastatic esophageal squamous cell carcinoma in China - Shi, Fenghao; He, Zixuan; Su, Hang; Wang, Lin; Han, Sheng (Frontiers in Pharmacology, 2022)
Background and purpose: The latest RATIONALE-302 trial (NCT03430843) showed that tislelizumab therapy significantly improved overall survival benefits for patients with advanced or metastatic esophageal squamous cell carcinoma (ESCC) compared with traditional chemotherapy. This study aimed to compare the cost-effectiveness of tislelizumab versus chemotherapy as a second-line treatment for advanced or metastatic ESCC in China. Methods: A partitioned survival model was developed to predict patients’ lifetime quality-adjusted life-years (QALYs) and incremental cost-effectiveness ratio (ICER) from the Chinese healthcare payers’ perspective. We extracted efficacy and safety data from the RATIONALE-302 trial and the local cost and resource use data from online databases and published studies. One-way sensitivity analysis (OWSA) and probabilistic sensitivity analysis (PSA) were performed to explore model uncertainty. Results: Compared with chemotherapy, tislelizumab generated a higher cost (US$ 10211.78 vs. US$ 7294.72) but yielded more QALY (0.78 vs. 0.51 QALYs). The ICER for tislelizumab was US$11073.85 per QALY gained. The PSA results indicated that the probability of tislelizumab being economical was 76% under a willingness-to-pay (WTP) threshold of 1.5 times per capita GDP ($17915) in China. Conclusion: Tislelizumab could be a promising cost-effective strategy as the second-line treatment for patients with ESCC compared with chemotherapy in the Chinese setting.